The effect of 3D virtual surgical planning in sacroiliac joint fusion - Nick Kampkuiper; Asal Abkar; Jorm Nellensteijn; Marjolein Brusse‐Keizer; Gabriëlle Tuijthof; Maaike Koenrades; Femke Schröder (Brain and Spine)
Background: Sacroiliac (SI) dysfunction causes of up to 30 % of lower back pain. When conservative treatment is insufficient, SI joint fusion (SIJF) can be indicated to reduce pain. Due to high anatomical variability, poor visibility during intraoperative 2D fluoroscopic imaging, and the absence of 3D spatial information, placing the implant in a stable configuration without damaging critical structures is challenging. To improve patient outcomes, a virtual surgical planning (VSP) method using simulated fluoroscopic images has been developed. Research question: What is the effect of VSP on patient outcomes, including complications, pain scores, satisfaction scores, and Oswestry Disability Index (ODI) scores? Methods: This retrospective case-control study compared procedures performed with VSP to those conducted prior to its implementation. Data were collected from the medical records, Numeric Rating Scale (NRS) questions, and patient reported outcome measures (PROMs). All postoperative CT scans were assessed on implant placement (mal)positioning and fractures. Malposition complications were categorized as severe malposition and suboptimal implant placement. Results: Seventy-eight procedures were included, 43 in the VSP group and 35 in the conventional group. Severe malposition complications reduced from 9 % to 0 % after VSP was implemented. Suboptimal implant placement reduced from 46 % to 9 % of the interventions. Sacral fractures reduced from 37 % to 14 %. All other primary outcome measures did not show a significant difference between the groups. Conclusions: VSP in SIJF reduced implant malpositioning and sacral fractures. This can lead to better patient outcomes. A larger multicenter study is needed to explore the broader impact of VSP on SIJF.